Factors Associated with Return to Work Postinjury: Can the Modified Rankin Scale be Used to Predict Return to Work?. Issue 2 (February 2016) - Kohli, Anirudh; Chao, Edward; Spielman, Daniel; Sugano, Dordaneh; Srivastava, Abhishek; Dayama, Anand; Lederman, Andrew; Stern, Michelle; Reddy, Srinivas H.; Teperman, Sheldon; Stone, Melvin E.
The ability to return to work (RTW) postinjury is one of the primary goals of rehabilitation. The modified Rankin Scale (mRS) is a validated simple scale used to assess the functional status of stroke patients during rehabilitation. We sought to determine the applicability of mRS in predicting RTW postinjury in a general trauma population. The trauma registry was queried for patients, aged 18 to 65 years, discharged from 2012 to 2013. A telephone interview for each patient included questions about employment status and physical ability to determine the mRS. Patients who had RTW postinjury were compared with those who had not (nRTW). Two hundred and thirty-four patients met the inclusion criteria. Of these, 171 (72.5%) patients RTW and 63 (26.7%) did nRTW. Patients who did nRTW were significantly older, had longer length of stay and higher rates of in-hospital complications. Multivariate analysis revealed that older patients were less likely to RTW (odds ratio = 0.961, P = 0.011) and patients with a modified Rankin score ≤2 were 15 times more likely to RTW (odds ratio = 14.932, P < 0.001). In conclusion, an mRS ≤2 was independently associated with a high likelihood of returning to work postinjury. This is the first study that shows applicability of the mRS for predicting RTW postinjury in a trauma population.